BPJS Barrier to Strategic Purchasing of Primary Care Service at Public and Private Health Facilities in Subulussalam, Aceh - Satria Darma; Juanita Juanita; R. Kintoko Rochadi (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Strategic purchasing plays an important role in the cost structure and competitiveness of small and large businesses. Managing Board of Social Insu-rance (BPJS) has implemented strategic purchasing of health services in the National Health Insurance (JKN) scheme. Strategic purchasing is important to provide quality products and services at low costs. Strategic purchasing of health service has five critical criteria: (1) what is to purchase; (2) to whom it is for; (3) whom it is from; (4) what is the price; (5) how to purchase it. This study aimed to assess BPJS barrier to strategic purchasing of primary care service at public and private health facilities in Subulussalam, Aceh.Subjects and Method: This was a qualitative study conducted in Subulussalam, Aceh, from February to July 2015. A total of 12 key informants for this study, including BPJS administrators and hospital managers. The theme was strategic purchasing of health service. The data were collected by in-depth interview, direct observation, and document review. The data was analyzed by thematic analysis.Results: BPJS administered the same standards of strategic purchasing health service from the public and private health providers. However, there were some unresolved problems: (1) BPJS faced difficulty to select primary care providers independently; (2) Illegal use of other members JKN card to get health service; (3) Redundant claims from the primary care providers; (4) Claim of inpatient days exceeding the maximum allowable limit; (5) Delay in non-capitations reimbur-sement payment to primary care provider; (6) Inequitable distribution of health manpower across health facilities.Conclusion: BPJS has implemented strategic purchasing of primary care services with the same standards applied to public and private primary care providers. However, there remain some problems of purchasing health services that call for immediate corrective actions, including routine monitoring, explanation of delay, advocacy, equitable distribution of health manpower.Keywords: strategic purchasing, primary care service, health facility, BPJS.Correspondence: Satria Darma. Department of Health Policy and Administration, Universitas Sumatera Utara, North Sumatera. Email: s4tria.darma@yahoo.com. Mobile: 085260077824.Journal of Health Polic and Management (2018), 3(2): 81-91https://doi.org/10.26911/thejhpm.2018.03.02.04